The Reasons and roles of the establishment of National Political Assembly (Guo Min Can Zheng Hui) - Xiang, Li; Suffian Mansor,; Azlizan Mat Enh, (Penerbit Universiti Kebangsaan Malaysia, 2024)
For nearly 80 years, the study of National Political Assembly (Guo Min Can Zheng Hui) has been a hot topic among scholars in mainland China. However there's a scarcity of deep research regarding the reasons and roles of National Political Assembly. This study aims to identify the reasons behind the establishment of National Political Assembly and to explore National Political Assembly’s role in uniting the Chinese. A qualitative research approach was employed, involving collecting primary and secondary historical materials in archives and libraries of China for literature analysis and case studies of representative events or proposals. The findings show that its establishment was related to Japan's aggression, the foreign policies of the United States, Britain, the Soviet Union and other countries, as well as the domestic anti-Japanese parties represented by the Kuomintang and the Communist Party of China, and the people of all walks of life across the country. This paper concludes that in the early days of its establishment, it played a positive role in China's unity against Japan, democratic politics, and economic stability. This research is extremely valuable for studying the history of China's Second Sino-Japanese War and the Second KMT-CPC Collaboration, as well as the economic policies, political proposals, and military strategies of the Kuomintang, the Communist Party of China, and other parties involved in the Second Sino-Japanese War, as well as the history of the Communist Party of China, the Republic of China, and modern Chinese history.